1993
DOI: 10.3109/08977199308991588
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Basic Fibroblast Growth Factor (bFGF) within Growing and Atretic Mouse Ovarian Follicles

Abstract: Basic fibroblast growth factor is a biologically active peptide with a strong affinity for heparin. This growth factor has been previously shown to be mitogenic for a variety of mesoderm and neuroectoderm-derived cells. The immunohistochemical localization of basic FGF within mouse growing and atretic ovarian follicles is presented in the study. Ovarian tissue samples were obtained either (a) randomly from mice housed in a controlled light environment or (b) following the administration of exogenous gonadotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…There was also no observable effect of FGF on progesterone secretion even though FGF expression has been detected in bovine luteal cells (Stirling et al 1990(Stirling et al , 1991. Others have detected, by immunocytochemistry, FGF in bovine large luteal cells (Schams et al 1993) while in another study, FGF was immuno-localised around luteal cells but lacked any cytoplasmic staining (Wordinger et al 1993). Clearly more information is required to clarify the exact role of FGF in the large luteal cell.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There was also no observable effect of FGF on progesterone secretion even though FGF expression has been detected in bovine luteal cells (Stirling et al 1990(Stirling et al , 1991. Others have detected, by immunocytochemistry, FGF in bovine large luteal cells (Schams et al 1993) while in another study, FGF was immuno-localised around luteal cells but lacked any cytoplasmic staining (Wordinger et al 1993). Clearly more information is required to clarify the exact role of FGF in the large luteal cell.…”
Section: Discussionmentioning
confidence: 90%
“…Since heparin binds FGF (Yayon et al 1991, Mansukhani et al 1992) and enhances FGF binding to its receptor (Roghani et al 199A) it is likely that this had a stimulatory effect in this experiment and enhanced the action of FGF on steroidogenesis. FGF also binds to components of the basal lamina in the follicle (Wordinger et al 1993) and to components of the extracellular matrix (Gonzalez et al 1990, Carlone & Rider 1993. It has been suggested that this binding is an important regulatory mechanism of FGF's cellular actions (Logan & Hill 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Mice lacking a functional FGFR-2 are not presently available. FGF may play important roles during gametogenesis, as bFGF has been detected both in murine ovarian follicles [39] and in rat spermatocytes [40]. Another member of this growth factor family, FGF-8, may also be present in prespermatogonia between 15 and 17 dpc [41].…”
Section: Discussionmentioning
confidence: 98%
“…Although this fact differentiates the armadillo's ovary from the mouse's one, in which this sort of primordial follicles are found exclusively in the prenatal stage (Wordinger et al, 1993), it resembles the ovary of other primitive mammals (Falconnier & Kress, 1992;Maitland & Ullmann, 1993).…”
Section: Discussionmentioning
confidence: 91%